THE EFFECT OF SPONSORSHIP ANNOUNCEMENTS ON STOCK RETURNS: DOES INDUSTRY CONCENTRATION MATTER? - Eryigit, Canan; Eryigit, Mehmet (PEOPLE: International Journal of Social Sciences, 2017)
The purpose of this paper is to provide an event study based evidence on whether the effect of sponsorship announcements on stock returns differs based on market concentration. The study sample includes 17 sponsorship announcements occured during the period of 2011 and 2016 for10 firms listed in BIST. In order to test whether stock return is affected by sponsorship announcements, abnormal return (AR), cumulative abnormal return (CAR) were tested by using t-tests for event window [-5, +5]. According to the results, in [-5 +5] event window 13 events revelaed statistically significant AR and CAR before and after the event day. Accordingly, sponsorship announcements are associated with stock returns of sponsoring firms. A Mann-Whitney U test indicated statistically significant difference in abnormal returns between firms operating in non-concentrated industries and firms in concentrated industries. In concentrated markets sponsorship announcements created negative abnormal returns. On the other hand, sponsorship announcements created positive abnormal returns in non-concentrated industries. The study extends the current knowledge through providing empirical evidence for the role of market competitive structure.